Analysis on the development of Chinese under-forest economy and its effect on the increase of farmers' income. (3rd October 2017) - Hou, Fang-Miao; Wu, Juan; Li, Hong-Xun; Yang, Ya-Lan; Luo, Xin-Jie; Shen, Yu
Abstract: As part of the construction of ecological civilization, the development of under-forest economy has been paid more and more attention. This paper uses DEA model to measure the development of under-forest economy. The results show that the development of the under-forest contributes to the increase of the output value, and thus promotes the growth of the farmers' income.